Establishing cell polarity in plants: the role of cytoskeletal structures and regulatory pathways - Ma, Chao; Chang, Jianbin; Hazelwood, Olivia S.; Arif Ashraf, M.; Nan, Qiong (Frontiers in Cell and Developmental Biology, 2025)
Cell polarity is a fundamental mechanism of plant cells that drives cellular specialization and the formation of diverse cell types. It regulates critical developmental events, including polarized tip growth (such as pollen tubes and root hairs), epidermal patterning (such as trichome branching and asymmetric cell division in stomata). The establishment and maintenance of cell polarity rely on the cytoskeleton-mediated polarized distribution of specific proteins and organelles. In particular, cell-type-specific actin and microtubule dynamic structures are pivotal for maintaining polarity. For example, actin cables and short actin fragments are critical for pollen tube growth, while actin clusters and microtubule rings are involved in trichome branching, and actin patches contribute to stomatal mother cell polarization. Beyond directing the polarization of organelles and proteins, the cytoskeleton itself serves as an intrinsic cue for polarity. For instance, actin patches in stomatal precursor cells act as self-organizing polarity landmarks. Despite the diversity of cytoskeletal structures and their functions, common regulators, such as Rop GTPase signaling pathways, WAVE/SCAR complexes, and motor proteins regulate the assembly and function of these structures. Recent advances have revealed new regulatory mechanisms, such as microtubule exclusion zones guiding asymmetric divisions during Arabidopsis stomatal development, and the role of actin rings in regulating xylem pit formation. These discoveries contribute to a deeper understanding of the cytoskeleton’s crucial role in polarity regulation. In this review, we highlight the key cytoskeletal structures involved in the establishment of cell polarity in plants and discuss the molecular mechanisms underlying their spatiotemporal assembly. We also address emerging questions regarding the cytoskeleton’s role in cell polarity and development.